The supply side of security : a market theory of military alliances. - Kim, Tongfi (Studies in Asian security., 2017)
'The Supply Side of Security' conceptualises military alliances as contracts for exchanging goods and services. At the international level, the market for these contracts is shaped by how many countries can supply security. It identifies the supply of policy concessions and military commitments as the main factors that explain the bargaining power of a state in a potential or existing alliance.